Impact assessment of additive manufacturing on sustainable business models in industry 4.0 context - Godina, Radu (2020)
POCI-01-0145-FEDER-016414 UIDB/00667/2020 PTDC/EME-SIS/32232/2017 UID/EMS/50022/2019